Impression of Company Size, Profitability, Earning Coefficient Response (ERC) Through Timeliness - Yulianti, Ani; Sulistya, Agung Budi; Sayekti, Yosefa (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2021)
This study examines how firm size and profitability can influence ERC through timeliness. This research is exploratory. The test model used is the path analysis model. The population used by this study are manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2014-2018 period. The method used in sampling is purposive sampling method. The number of companies that met the assessment criteria was 58 companies, so that the number of observations during 2014 - 2018 was 290 observations. Data collection techniques using documentation data. The data analysis technique in this study used descriptive statistics and classical assumption tests and path analysis. Based on the results, it can be concluded that company size and profitability do not have a positive effect on timeliness, company size and profitability that are interacted with the EU has no effect on ERC, while the timeliness of submitting financial reports that are interacted with the EU has an effect on ERC. Firm size and profitability have no effect on ERC with timeliness as an intervening variable.